Prognostic value of N-terminal Pro–B-Type natriuretic peptide in patients with intermediate coronary lesions - Song, Chenxi; Yuan, Sheng; Cui, Kongyong; Cai, Zhongxing; Zhang, Rui; He, Jining; Qiao, Zheng; Bian, Xiaohui; Wu, Shaoyu; Wang, Haoyu; Fu, Rui; Wang, Chunyue; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: The optimal treatment strategy for patients with coronary intermediate lesions, defined as diameter stenosis of 50%-70% remains a great challenge for cardiologists. Identification of potential biomarkers predictive of major adverse cardiovascular events (MACE) risk may assist in risk stratification and clinical decision. Methods: A total of 1187 patients with intermediate coronary lesions and available NT-proBNP level were enrolled in the current study. Baseline NT-proBNP level was obtained. Primary endpoint was defined as major adverse cardiovascular events (MACE), the composite endpoint of all-cause death and non-fatal myocardial infarction. Multivariate Cox regression model was used to explore the association between NT-proBNP level and MACE risk. Results: Mean age of the study cohort was 59.2 years. A total of 68 patients experienced MACE during a median follow-up of 6.1 years. Restricted cubic spline analysis delineated a linear relationship between baseline NT-proBNP level and MACE risk. Both univariate and multivariate analysis demonstrated that elevated NT-proBNP level was associated with increased MACE risk (adjusted hazard ratio per doubling: 1.412, 95% confidence interval: 1.022-1.952, P=0.0365). This association remains consistent in clinical meaningful subgroups according to age, sex, and body mass index. Conclusions: Elevated NT-proBNP is associated with increased MACE risk in patients with intermediate coronary lesions, and may serve as the potential biomarker for risk stratification and treatment decision guidance.